Caracterização morfofisiológica e genética de bactérias endofíticas isoladas de arroz (Oryza sativa) - (:unkn) unknown (Universidade Estadual de Goiás, 2012)
Rice is among the most cultivated cereals in Brazil. Besides, rice is the most important cereal in the human diet worldwide. Research projects with focus on beneficial micro-organisms to rice growth, providing environmental protection and allowing lower cost of production are of great importance. The objective of this study was to characterize genetic and morphophysiologically twenty bacteria isolated from rice which can further be used as plant growth promoting rhizobacteria (PGPR). In this study it were observed the morphological and physiological characteristics of the colonies regarding their capacity of utilization of thirteen carbon sources and the presence of enzymes (catalase, citrate lyase, nitrate reduction and urease). Genetic analyses of the 20 bacteria by BOX-PCR and 16S rDNA amplification were also performed. In addition, the partial sequencing of the 16S rDNA was also carried out for 17 bacteria. The results of 15 bacteria were analyzed by similarity clustering using the Jaccard coefficient. According to the morphological data it was observed the formation of 2 groups. Clustering analysis using the biochemical data based on carbon sources use by the bacteria showed the distribution of the bacteria into eight groups. According to the presence of enzymes, all bacteria were catalase positive, 45% citrate positive, 65% reducing nitrate, 20% urease positive, 40% hydrolases of proteins and 85% potential biological nitrogen-fixing. From these results it was possible to observe a great metabolic diversity among the studied bacteria. BOX-PCR results showed the distribution of the isolates into five groups showing the genetic variability of the bacteria associated with the rice plant. 16S rDNA sequencing analysis resulted in the description of three bacterial genera associated to rice plants, indicating the predominance of the genus Bacillus sp.. This characterization may assist in the selection of bacteria candidates to be used in trial assays under in vitro and field conditions for the crop of rice in of Goiás savanna.
Keywords: Arroz; Bactérias promotoras de crescimento vegetal; Caracterização bioquímica; Caracterização molecular; Rice; Plant growth promotion rhizobacteria; Biochemical Characterization; Molecular Characterization; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::QUIMICA ORGANICA